Migrants and Foreign Language Learners in Pokhara Metropolis: Attitudes towards National Development - Magar, Lalit (Academia Journal of Humanities & Social Sciences, 2024)
In Pokhara Metropolis, the trend of international migration has been a dominant issue in modern times. Many agree that globalization is one of the main reasons behind this migration to the rest of the world. Thus, it has become evident that there is a growing trend of migration especially among the youths of the country. Specifically, acquisition of languages is one of the factors for this migration trend. There is a growing tendency among the youths to learn languages to migrate in different parts of the world as a student or a migrant worker. This study attempts to find out the interrelationship between language acquisition and migration. Language proficiency has become a social norm for migrants of Pokhara Metropolis. In this regard, this study purposes to explore how languages of the host countries play crucial roles to get access to migrant labor force in different parts of the world to generate national revenue. This research paper has applied mixed methods. In order to collect data, surveys, observations, interviews, and focus group discussions have been taken into account. At the same time, the sources of secondary data have been used to bring a conceptual framework for research. The study concluded that the aptitude of language learners is remarkable to get access to other countries as a migrant labor force to generate national revenue for the country.